APPLYING INSIDE-OUTSIDE CIRCLE COOPERATIVE LEARNING TO IMPROVE FIFTH-GRADE SCIENCE LEARNING OUTCOMES - Anisa Rahim (Teaching and General Education Studies, 2026)
Science learning in elementary schools often faces challenges such as low student participation and limited learning media, which can affect students’ achievement. Therefore, this study aims to examine whether the Inside-Outside Circle (IOC) cooperative learning model assisted by question card media can improve science learning outcomes of fifth-grade students. The research was conducted at SD Negeri 60 Lubuklinggau using Classroom Action Research with the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were Grade V students. Data were collected through tests, observations, and documentation, and analyzed using descriptive qualitative and descriptive quantitative techniques. The findings showed improvement in students’ science achievement in each cycle. In Cycle I, the average pre-test score was 56.42 and the post-test score increased to 63.80. In Cycle II, the average pre-test score was 70.47 and the post-test score reached 76.66, with a gain score of 0.3 (moderate). In conclusion, the IOC model supported by question cards effectively improves students’ science learning outcomes. It is suggested that teachers apply this strategy regularly and develop varied question cards to maintain students’ engagement.